Artificial Intelligence and Student Learning Practices: A Study ofUrban Higher Education in Odisha (Global Journal of Human-Social Science, 2025)
This study examines the adoption patterns of artificial intelligence AI among higher education students in urban Odisha India emphasising both general and academic applications Data were collected from 100 students at four major urban universities in Odisha through an online quantitative survey using Google Forms and analysed the data collected using descriptive statistics and the non-parametric Mann-Whitney U test to evaluate the impact of demographic factors on AI engagement The results indicate that the utilisation of AI for both general activities including information retrieval translation and entertainment and academic endeavours such as research writing and exam preparation is prevalent and predominantly unaffected by demographic factors such as gender age academic standing family structure and field of study This demographic neutrality underscores AI s widespread allure indicating that its incorporation into higher education has the capacity to surpass conventional social and institutional barriers Percentage trends indicate subtle variations in user behaviours however these variations lack statistical significance underscoring the necessity for user-centric methodologies that transcend general demographic classifications The study emphasises the significance of utilising AI to democratise education and guide inclusive policy and curriculum development especially in under-represented areas such as Odisha These insights contribute to the discourse on AI in education by demonstrating its potential to promote equitable access and tailored learning environments while also indicating avenues for sophisticated qualitative research on individual motivations and longitudinal trends in AI adoption
Keywords: artificial intelligence (AI); higher education; urban odisha students; demographic variables